Preparation of fluoride adsorbent by resource utilization of carbide slag from industrial waste. Issue 6 (December 2022) - Ren, Yuanchuan; Tong, Jia; Qu, Guangfei; Ning, Ping; Ren, Nanqi; Zhang, Chaoneng; Wu, Fenghui; Yang, Yuyi; Chen, Xiuping; Wang, Zuoliang; Hu, Yan; Wang, Jun; et al.
Abstract: A high performance fluoride adsorbent was prepared for the removal of fluoride from industrial wastewater by calcination and polyacrylic acid impregnation. Through batch experiments, the removal capacity of the adsorbent for fluorine and the influence of key factors (calcination temperature, dosage of polyacrylic acid, pH, initial fluorine concentration and dosage of adsorbent) on the efficiency of the adsorbent for fluoride removal was investigated. The maximum adsorption capacity and removal of efficiency were 98.61 mg/g and 98.7%, respectively. The adsorption kinetics and isotherm studies showed that the pseudo second order model and Langmuir isotherm model fitted this adsorption process better. Moreover, the mechanism of F − removal by CS, C-CS, PAA@C-CS were further analyzed by SEM, EDS, XRD and FTIR. F - in wastewater were found to be adsorbed on the surface of adsorbent through electrostatic interaction, ion exchange and surface coordination. Recovery is achieved by desorption of the adsorbent material by NaOH (0.1 M). As a highly resourced and eco-friendly adsorbent for removal of F − from industrial wastewater, PAA@C-CS has a promising application for controlling industrial water pollution. Graphical Abstract: ga1 Highlights: A simple and economical method was used for defluorination of wastewater. PAA@C-CS were efficient for the removal of low fluoride content. Fluoride removal occurred simultaneously by ion exchange, surface coordination and electrostatic attraction. The method overcame the limitation of solid waste in applications.